Empathy and the strangeness of fiction : readings in French realism - Scott, Maria C., 1972- (Edinburgh University Press Ltd, 2020)
This book studies recent psychological findings which suggest that reading fiction cultivates empathy, encouraging us to be critically reflective, suspicious readers as well as participatory, 'na ve' readers. Scott draws on literary theory and close readings to argue that engagement with fictional stories also teaches us to resist uncritical forms of empathy and reminds us of the limitations of our ability to understand other people. The book treats figures of the stranger in Balzac's La Fille aux yeux d'or, Stendhal's Le Rouge et le Noir and Sand's Indiana as emblematic of the strangeness of narrative fiction, both drawing us in and keeping us at a distance.